Percutaneous full-endoscopic uniportal decompression for the treatment of symptomatic idiopathic lumbar spinal epidural lipomatosis: Technical note - Yu, Yong; Jiang, Ye; Xu, Fulin; Yuan, Lutao; Mao, Yuhang; Li, Chen (Frontiers in Surgery, 2022)
Background: Lumbar spinal epidural lipomatosis (SEL) is a rare condition characterized by excessive overgrowth of extradural fat within the lumbar spinal canal. Surgical decompression will be considered when clinical symptoms are acute and severe or conservative treatments have failed. The indications of percutaneous endoscopic spine surgery are ever expanding, with the development of endoscopic armamentaria and technological innovations. Objective: In this paper, the authors describe a patient with lumbar spinal epidural lipomatosis who was successfully treated with a percutaneous full-endoscopic uniportal technique. The purpose of this report is to validate the feasibility of percutaneous full-endoscopic uniportal decompression for the treatment of symptomatic idiopathic spinal epidural lipomatosis via interlaminar approach. Methods: We describe a case of a 69-year-old man (weight, 70 kg; height, 172 cm; and body mass index, 23.66 kg/m2) with a 10-year history of low back pain，bilateral leg radicular pain and neurogenic intermittent claudication who did not respond to physical therapy and drug therapy. After careful examination, we performed a percutaneous full-endoscopic uniportal surgery to remove the lipomatosis. Results: The patient was successfully treated with a percutaneous full-endoscopic uniportal decompression. After the procedure, the patient felt better with the improvement of leg pain and walking capacity. There was no CSF leakage, incision infection, or other complications. Conclusions: SEL can be accomplished successfully using a percutaneous full-endoscopic uniportal technique under continuous irrigation, which has the advantages of excellent presentation of anatomical structures, expanded field of vision, reduced traumatization and reduced bleeding. It is important to release and cut off the bands that divide the epidural space into small rooms filled with excess fat.